PENGARUH PENGGUNAAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL KELAS V SEKOLAH DASAR NEGERI 21 PONTIANAK TIMUR - Alidrus, Khairun Nisah; Sugiyono, Sugiyono; Salimi, Asmayani (Universitas Tanjungpura, 2023)
he purpose of this research is to analyze the influence of Mind Mapping model to the learning result of social science from elementary school number 21, east Pontianak. The research sample is class five B as an experimental class and class five A as a control class. It forms multiple choice that consist of 50 questions. The average result of post test in experimental class is 80,55 and 76,34 for the control class.After analyzing with T test, this is gotten T count that's amount of 3,322 and T table a = 5% (with di = 32 + 32 - 2=62) amount of 1,994. It means that T count is bigger than T table.Then, ha is received. Therefore, it can be concluded that there is an influence of mind mapping model to the learning result of social science from class five students in elementary school number 21 east PontianakFrom the counting of effect size(ES), it gets ES that's amount of 0,81 (high criteria). It means that mind mapping model gives high influence to the learning result of students class five in social science of elementary school number 21 east Pontianak.